Titanium elastic percutaneous nails for pediatric long bone shaft fractures: current concept (Bangladesh Journal of Medical Science, 2017)
Introduction: The objective of this study was to determine the effectiveness and the complications associated with elastic stable intramedullary nailing in long bone fractures in children.Methods: This study was conducted in the Department of Orthopaedic surgery in M. M. Medical College from July 2006 to November 2009. Eighty two patients were recruited from Emergency and out patient department having closed fracture of long bones of upper and lower limbs. All patients were operated under general or spinal anaethesia. All patients were followed for twelve months.Results: All children achieved union in a mean time of 10 weeks (range from 6 - 16 weeks) depending on the type of long bone. Full weight bearing was possible in a mean time of 8.8 weeks. Mean duration of hospital stay was 9.8 days. The mean follow-up period was 28 months (17-48 months). Complications were recorded in 5 (6.09%) patients and included: two entry site skin irritations, one protrusion of the wires through the skin and two delayed union. The results were excellent in 97.310% and good in 2.44% patients.Conclusion: We concluded that this technique is advantageous because of early mobilization (early weight bearing), less complication with good results and is economical.Bangladesh Journal of Medical Science Vol.16(1) 2017 p.61-68